Biogas (a promising bioenergy source): A critical review on the potential of biogas as a sustainable energy source for gaseous fuelled spark ignition engines. (8th March 2023) - Gupta, Priyank; Kurien, Caneon; Mittal, Mayank
Abstract: Increasing demand for energy accompanied by environmental concerns has raised the requirement for limiting the use of fossil fuels in energy generation and transportation applications. Among the green and renewable energy-based solutions, biogas is quite promising since it could be implemented for power generation applications (engines driving generators and pump sets) in rural areas, at domestic and industrial scales with lower capital investment and production cost by using the agricultural crop residues and other domestic biomass sources as raw materials. However, the composition of biogas varies depending on the raw materials, and higher concentration of carbon dioxide in biogas results in combustion variations affecting engine durability. This review focuses on the role of biogas in achieving sustainable development goals with an emphasis on its utilization in gaseous fuelled spark-ignited engines. Recent progress in biogas production and upgradation techniques are also detailed. Challenges related to the stability and characteristics of biogas fuelled spark-ignited engines could be addressed by either modifying the physical parameters of the engine or by enhancing the fuel quality (upgradation to biomethane or blending with hydrogen). A comprehensive review on the effects of these approaches on the performance, combustion, and emission characteristics of biogas-fuelled engines is discussed in detail with a note on engine operating parameters. Highlights: Literature study on the engine characteristics of biogas fuelled SI engines. Biogas as a fuel for decarbonization of power generation and transportation sector. Nature and impact of biogas impurities with challenges for deployment of biomethane. Future outlook for biogas cleaning, upgradation and utilization are suggested.